SOME ASPECTS OF THE PREPARATION OF EMPLOYEES OF THE PRELIMINARY INVESTIGATION BODIES FOR THE USE OF FIREARMS - V. Kalinin; E. Vasilenko; N. Kryzhevskaya (Вестник Северо-Кавказского федерального университета, 2022)
The analysis of the state of crime in Russia, the presence of clear trends of its growth, aggressiveness and brutality of the criminal society against the background of its modern equipment makes the problem of professional psychological and pedagogical readiness of police officers to use and use firearms in operational and official activities particularly relevant. With the occurrence of an extreme situation, the employee's actions and behavior are determined by the level of professional training and willingness to manage their mental state. As practice shows, the facts of death and injuries occur not only because of the increased aggressiveness of criminals, but also because the personnel are professionally not ready for a collision with criminals. Thus, in fire training classes, it is necessary to pay special attention not only to the technical skills of using firearms, but also to the psychological readiness to use them.